Single Session Counseling Integrated with Expressive Art to Improve Students' Internet Altruistic Behavior - Suargani, Ganjar; Mulawarman, Mulawarman; Awalya, Awalya (Jurnal Kajian Bimbingan dan Konseling, 2022)
The internet is one of the means to obtain information, interact, and even provide help to others. To be able to give voluntary help based on empathy, one must have internet altruistic abilities. This study aims to determine the effectiveness of single-session counseling with expressive art integration to improve students’ altruistic behavior on the internet. This study used a randomized pretest-posttest control group design. The intervention in the experimental group used a single session counseling strategy that was integrated with expressive art. The control group was given an intervention in the form of individual counseling without using a single session counseling approach. Research subjects were selected using random assignment to the experimental group or the control group according to the established criteria. The data was collected by giving the Internet Altruistic Behavior Scale (IABS) psychological scale which was adapted according to scientific rules with a reliability of 0.92. The data analysis used was mixed ANOVA repeated measure. The results showed that single session counseling with expressive art integration was effective in increasing students’ altruistic behavior on the internet. Further research is recommended to expand the scope of research subjects, and be able to analyze gender and age differences between research subjects.